Subcritical hydrothermal conversion of organic wastes and biomass. Reaction pathways - Alejandro Amadeus Castro Vega (Ingeniería e Investigación, 2007)
Hydrothermal conversion is a procedure which emulates organic matter’s natural conversion into bio-crude having physical and chemical properties analogous to petroleum. The artificial transformation of biomass requi- res previous knowledge of the main reaction routes and product availability. The main component of biomass (depolymerisation by hydrolysis) is presented in hydrothermal cellulose conversion, producing oligosaccharides which exhibit dehydration and retro-aldol condensation reactions for transforming into furfurals and carboxylic acids. Other biomass components (such as lignin, proteins, and fat esters) present both hydrolysis and pyrolysis reaction routes. As long as biomass mainly contains carbohydrates, subcritical hydrothermal conversion products and their wastes will be fundamentally analogous to those displaying cellulose. These substances have added- value by far surpassing raw material’s acquisition cost. When the main hydrothermal conversion products’ O/C, H/C molar ratios as reported in literature are plotted, an evolutionary tralectory for conversion products appears to be closely or even overlapped with fossil fuels’ geological evolution.